r = 1 ∑ 1 1 7 2 ⌊ r ⌋ + 1 1 = b a
If the equation above holds true for positive coprime integers a and b , enter a + b + 2 as your answer.
Notation: ⌊ ⋅ ⌋ denotes the floor function .
For more problems try my new set
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you convert it into integral?
Log in to reply
Simply by observing
∫ 0 1 x n d x = n + 1 1
we can put n = 2 ⌊ r ⌋ .
I didnt understand your 4th step. How did the summation limit got changed to 1 to 9.
Log in to reply
Simply observing that if r lies between two perfect squares k 2 and ( k + 1 ) 2 then
⌊ r ⌋ = k for r ∈ [ k 2 , ( k + 1 ) 2 − 1 ]
Now between k 2 and ( k + 1 ) 2 − 1 , there are a total of 2 k + 1 integers. Thus between a perfect square and the preceding integer of the next perfect square we'll get 2 k + 1 terms of 2 ⌊ r ⌋ = 2 k .
Further observe that these intervals are
[ 1 , 3 ] ; [ 4 , 8 ] ; [ 9 , 1 5 ] ; [ 1 6 , 2 4 ] ; [ 2 5 , 3 5 ] ; [ 3 6 , 4 8 ] ; [ 4 9 , 6 3 ] ; [ 6 4 , 8 0 ] ; [ 8 1 , 9 9 ]
With each respective interval giving us the value of ⌊ r ⌋ from 1 to 9. The last interval, i.e., from [ 1 0 0 , 1 1 7 ] isn't exactly ending as a preceding digit of the next perfect square (which in this case would be 120), so we can just simply count the number of these which is 1 8 and here ⌊ r ⌋ = 1 0 ⟹ 2 ⌊ r ⌋ = 2 0 .
S = r = 1 ∑ 1 1 7 2 ⌊ r ⌋ + 1 1 = r = 1 2 3 1 + 3 1 + 3 1 2 2 − 1 2 terms + r = 2 2 5 1 + 5 1 + . . . + 5 1 3 2 − 2 2 terms + r = 3 2 7 1 + 7 1 + . . . + 7 1 4 2 − 3 2 terms + . . . + r = 1 0 2 2 1 1 + 2 1 1 + . . . + 2 1 1 = k = 1 ∑ 9 2 k + 1 ( k + 1 ) 2 − k 2 + 2 1 1 8 = k = 1 ∑ 9 2 k + 1 2 k + 1 + 7 6 = k = 1 ∑ 9 1 + 7 6 = 9 + 7 6 = 7 6 9
⟹ a + b + 2 = 6 9 + 7 + 2 = 7 8
S = r = 1 ∑ 1 1 7 2 ⌊ r ⌋ + 1 1
S = 3 1 + 3 1 + 3 1 + 5 1 + 5 1 + 5 1 + 5 1 + 5 1 + . . . + 2 1 1
S = 3 ⋅ 3 1 + 5 ⋅ 5 1 + 7 ⋅ 7 1 + 9 ⋅ 9 1 + 1 1 ⋅ 1 1 1 + 1 3 ⋅ 1 3 1 + 1 5 ⋅ 1 5 1 + 1 7 ⋅ 1 7 1 + 1 9 ⋅ 1 9 1 + 1 8 ⋅ 2 1 1
S = 6 + 7 6
S = 7 6 9
So:
a = 6 9 , b = 7 , a + b + 2 = 7 8
Problem Loading...
Note Loading...
Set Loading...
S = r = 1 ∑ 1 1 7 2 ⌊ r ⌋ + 1 1 = r = 1 ∑ 1 1 7 ∫ 0 1 x 2 ⌊ r ⌋ d x = ∫ 0 1 ( r = 1 ∑ 1 1 7 x 2 ⌊ r ⌋ ) d x = ∫ 0 1 ( n = 1 ∑ 9 ( 2 n + 1 ) x 2 n + 1 8 ⋅ x 2 0 ) d x = n = 1 ∑ 9 ∫ 0 1 ( 2 n + 1 ) x 2 n d x + ∫ 0 1 1 8 ⋅ x 2 0 d x = n = 1 ∑ 9 ( 1 ) + 2 1 1 8 = 9 + 7 6 = 7 6 9 ⟹ a + b + 2 = 6 9 + 7 + 2 = 7 8